2021
DOI: 10.1159/000516906
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-425-5p Is Involved in the Development of Diabetic Retinopathy and Regulates the Proliferation and Migration of Retinal Microvascular Endothelial Cells

Abstract: <b><i>Introduction:</i></b> The objective of this article was to detect the expression pattern and clinical value of miR-425-5p in diabetic retinopathy (DR) patients and investigate its effect on the proliferation and migration of human retinal microvascular endothelial cells (HRMECs) in a high glucose (HG) state. <b><i>Methods:</i></b> The serum miR-425-5p level of the subjects was determined using quantitative real-time PCR. The diagnostic value of serum miR-42… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In total, 25 documents (spanning years 2014 to 2022) included in this meta-analysis involved 52 studies ( 11 , 18 , 20 , 25 46 ) ( Table 1 ), all of which were case-control studies that included a total of 1987 patients with DR and 1771 non-DR controls, with the source of controls being diabetic patients not diagnosed with DR, healthy population, and patients with cataract. Among these 52 studies, 41 studies reported a single miRNA, and 11 studies discussed a panel of miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 25 documents (spanning years 2014 to 2022) included in this meta-analysis involved 52 studies ( 11 , 18 , 20 , 25 46 ) ( Table 1 ), all of which were case-control studies that included a total of 1987 patients with DR and 1771 non-DR controls, with the source of controls being diabetic patients not diagnosed with DR, healthy population, and patients with cataract. Among these 52 studies, 41 studies reported a single miRNA, and 11 studies discussed a panel of miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…The blood glucose level of the mice was detected, and compared with the NC group, the blood glucose of DM mice increased significantly and was greater than 16.7 mmol/L. Glycated hemoglobin is an important standard for diabetes diagnosis and treatment monitoring, and the increase of glycated hemoglobin can promote the frequency of DR lesions (Liu et al 2022c ). And the glycated hemoglobin level was also significantly increased in the DM group.…”
Section: Resultsmentioning
confidence: 99%
“…DR is characterized by hyperglycemia, which causes changes in retinal microvascular function and integrity, leading to progressive retinal ischemia and angiogenesis (Deng et al 2022 ). In the treatment of DR, the first is to control blood sugar or to delay the occurrence of DR by changing lifestyle, improving insulin resistance and repairing damaged islet cell function, or to treat DR by laser surgery, vitrectomy and other treatments (Deng et al 2022 ; Liu et al 2022a , b , c ). However, the current treatment results of DR are often unsatisfactory, so it is necessary to explore more specific and precise molecular mechanisms to determine more effective prevention and treatment of DR.…”
Section: Introductionmentioning
confidence: 99%
“…After 3 months of treatment with empagliflozin, miR-21 and miR-92 were significantly reduced and endothelial dysfunction was alleviated in patients with heart failure with preserved ejection fraction ( 90 ). MiR-18b ( 79 ), miR-20b-5p ( 80 ), and miR-425-5p ( 91 ) promoted HRMEC proliferation and migration. Down-regulated MiR-126-3p in diabetic rat retina attenuates experimental diabetic retinopathy by targeting PLK4 to inhibit endothelial cell proliferation and migration ( 81 ).…”
Section: Microrna Intensification Of Diabetic Retinal Neurodegenerati...mentioning
confidence: 99%